2018
DOI: 10.1101/gr.233098.117
|View full text |Cite
|
Sign up to set email alerts
|

Damage-responsive elements in Drosophila regeneration

Abstract: Service Email Alerting click here. top right corner of the article or Receive free email alerts when new articles cite this article-sign up in the box at the http://genome.cshlp.org/subscriptions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 86 publications
(129 reference statements)
2
66
0
Order By: Relevance
“…We report thousands of accessible regulatory sequences (THSs) involved in tissue-specific transcriptional regulation, which were distributed genome-wide, particularly at introns and promoters (regions 1 Kb upstream of genes). This pattern is in agreement with the distribution of accessible regulatory sites reported in Drosophila by ATAC-seq (25,82), and in Ae. aegypti and An.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We report thousands of accessible regulatory sequences (THSs) involved in tissue-specific transcriptional regulation, which were distributed genome-wide, particularly at introns and promoters (regions 1 Kb upstream of genes). This pattern is in agreement with the distribution of accessible regulatory sites reported in Drosophila by ATAC-seq (25,82), and in Ae. aegypti and An.…”
Section: Discussionsupporting
confidence: 91%
“…The concentration of accessible sites within introns has been previously reported, for example in D. melanogaster tissues, with around 50% of ATAC-seq THSs found within introns (82). The density of THSs at promoters diminishes with distance from the TSS.…”
Section: Chromatin Accessibility Correlates With Active Transcriptionmentioning
confidence: 70%
“…This phenomenon was explained by the identification of bipartite damageresponse enhancers, which contain an activator region that induces gene expression upon disc damage, and a repressor region that mediates silencing of the enhancer via chromatin changes when ecdysone levels peak before pupariation (Harris et al, 2016). Tissue ablation methods have also been coupled with genomic approaches such as transcriptional profiling and chromatin profiling in an attempt to understand the mechanisms that drive regeneration (Khan et al, 2017;Vizcaya-Molina et al, 2018). Indeed, ATAC-seq profiling of regenerating wing discs at multiple time points has identified many regions with increased chromatin accessibility, suggesting changes in enhancer activity across the genome (Vizcaya-Molina et al, 2018).…”
Section: Regulating Regeneration Gene Expressionmentioning
confidence: 99%
“…Tissue ablation methods have also been coupled with genomic approaches such as transcriptional profiling and chromatin profiling in an attempt to understand the mechanisms that drive regeneration (Khan et al, 2017;Vizcaya-Molina et al, 2018). Indeed, ATAC-seq profiling of regenerating wing discs at multiple time points has identified many regions with increased chromatin accessibility, suggesting changes in enhancer activity across the genome (Vizcaya-Molina et al, 2018). Such damage-responsive enhancer elements have also been identified in acoel worms as well as in zebrafish and mouse hearts (Gehrke et al, 2019;Kang et al, 2016;Wang et al, 2019).…”
Section: Regulating Regeneration Gene Expressionmentioning
confidence: 99%
“…The capacity to regenerate relies not only on the presence/absence of certain genes but also on regulatory non-coding regions. By combining RNA-Seq and ATAC-Seq, Elena Vizcaya Molina (Corominas and Serras laboratory; University of Barcelona, Spain) identified the genomic map of damage-responsive enhancers that are active during Drosophila regeneration and showed that Drosophila imaginal discs, zebrafish heart and mouse liver share a core set of conserved genes required for regeneration (Vizcaya-Molina et al, 2018).…”
Section: New Approaches and Perspectivesmentioning
confidence: 99%